Islam dan masyarakat muslim di Filipina: kajian mengenai isu dan cabaran dalam pemikiran Islam era globalisasi - Wan Ali, Wan Zailan Kamaruddin; Ismail, A.Z. (APIUM, 2012)
Research on Islam and Filipino Muslim in Philippines gives us a lot of opportunities to know every Muslim in this region on their main concerns and problems with regards to Islam. It seems that Muslims in Philippines and the rest of the world are facing the problems from within and outside. There is a need to look into these issues so as to find ways to overcome and to solve it within Islam and their close connection with other Muslims. Malaysia in particular plays important role with the Muslim especially in the Mindanao and the surrounding areas due to its close relationship in terms of the history of the Muslim community in Malaysia since the early relationship, historically and religiously. Hence, this research aims to study various issues such as sources, methodology, key issues concerning the field of Islamic Thought faced by Filipino Muslim community. Furthermore, it also aims to understand the challenges and its forms, whether internal, his external, top-down, bottom-up, and so forth that are bothering them. This will be done by using two approaches or methods, the library and field research (fieldwork) especially interview. The findings show that Islam and Filipino Muslim in Philippines face many critical issues and challenges in the era of globalization from various factors, internally and externally that put them either in positive or negative situation. By understanding and sharing their problems, we can learn the way to move forward and foresee the challenges ahead for our own survival in the short and long term.